Working children and adolescents in the El Porvenir district, Trujillo – La Libertad (SCIÉNDO INGENIUM, 2021)
The research contextualizes child labor as a survival strategy in extremely poor families, to generate economic resources that barely meet their basic needs. This situation seriously violates the fundamental human rights of children and adolescents, being necessary to describe the context of child labor and the intervention to implement social policies at the local and regional level that include care plans and programs, committing the different actors responsible for civil society, business, local and regional government. According to the end, the research was applied, with a mixed approach, we worked with quantitative data to describe the general data of the population, children and adolescents who work on the streets of the El Porvenir district, province of Trujillo, La Libertad; Likewise, the interviews and focus groups allowed us to obtain valuable data to understand and describe the sociocultural patterns of the families and society involved, the research makes visible the urgent need to articulate efforts to address this problem within the framework of human rights.
Keywords: child labor; social politics; vulnerable population; human rights